Cities and Geographical Locations with Gods’ Names in the Light of Cuneiform Texts " - عامر عبدالله الجميلي ا.د. (lark, 2020)
" You, Judah, have as many gods as you have towns; and the altars you have set up to burn incense to that shameful god Baal are as many as the streets of Jerusalem.’” - Jeremiah 11:13/ Old Testament Thus, the Prophet Jeremiah described the influence of the Jews of Babylonian exile on the basis of adopting the principles of Babylon religious beliefs of polytheism and Idolatry, like the rest of Mesopotamia, even after returning from the period of deportation to their homeland Jerusalem in Palestine in the 6th century B.C. The inhabitants of Mesopotamia obviously took a great care for their gods and allocated cult centers in most cities of ancient Iraq and they built temples and renovated them and threw them out of their care, which they believed gave them their help and care throughout their lives, and religion had a big share in their lives it is the one whom determines the behavior of human beings and organizes their customs, traditions, and the judge of treatment of the individual in that society and a reflection and a mirror to form a nature of the connections, connecting him with the surroundings in which they lives, the people believed that there is a large number of goddesses reached 3000 and documented by their cuneiform scripts, as it organized the affairs of the world and the universe and took care of the interests of human beings on earth and the different preference of gods from others was in the complex of the divine gods (Pantheon): trinity, savoy and others according to the service they provide to humans in their daily lives. Each aspect and elements of nature or a matter of life or a general phenomenon were Identified by a god and the triangle of the goddess in the shape of symbols and signs, and what we are interested in in this regard is the allocation of certain cities by the names of those many gods as a kind of veneration or The replacement of the blessing upon them when they called these nomenclature and their names, and some of them may represent an mortmain property to the temples of God in other centers of god, income for the permanence and recovery of temples, provided by the fields and orchards of agricultural benefits, yields, crops and food.